Energy Policy and Poverty: A Study of the Effects of Fuel Prices in Indonesia - Didin Muhafidin (GoAcademica Research & Publishing, 2023)
The purpose of this article is to examine the effects of the Indonesian government's oil fuel price policy on the nation's poverty rate. This study investigates how variations in oil fuel costs affect the population's ability to make purchases, particularly those who are below the poverty line. It does so by using secondary data from a variety of sources and quantitative analysis techniques. According to the study's findings, the oil industry's gasoline pricing strategy significantly affects the poverty rate because rising fuel costs tend to make people poorer. According to this article, the government should think about the socioeconomic repercussions of its energy policy and look for ways to lessen the effects of rising fuel prices. The study adds to the body of knowledge on energy and poverty policies in Indonesia by offering new insights into the relationship between energy policy and poverty.